«Enfance en poésie», a collection of albums of classic poems? - Boutevin, Christine Paulette (Ondina - Ondine, 2023)
From the very beginnings of state-mandated schools in France, literary anthologies have been a means of disseminating poetry to children. But for a long time, these works were published only as paperbacks. Published collections for this genre came about late and struggled to find a lasting place. Gallimard’s collection «Enfance en poésie», launched in 2000, now offers a set of volumes in which classical authors are honored. However, in addition to a desire to transmit a cultural heritage is the need to adapt the format not only to its audience, but also to a cultural context and to a certain heter-ogeneity in the ways in which it is conveyed. Keywords : poetry, anthology, album, classical, children.